Silent Spontaneous Uterine Rupture at 36 Weeks of Gestation. (19th August 2015) - Woo, J. Y.; Tate, L.; Roth, S.; Eke, A. C.
Abstract : Introduction. Silent spontaneous rupture of the uterus before term, with extrusion of an intact amniotic sac and delivery of a healthy neonate, with no maternal or neonatal morbidity or mortality is very rare. Very few cases have been reported in literature. Case Presentation. We report a case of silent spontaneous uterine rupture, found during a scheduled repeat cesarean section at 36 weeks of gestation. Patient had history of two prior classical cesarean sections. She underwent cesarean section, with delivery of a healthy male infant. She had a good postoperative recovery and was discharged on postoperative day 3. Conclusion. Silent spontaneous rupture of the uterus before term with extrusion of an intact amniotic sac is rare. A high index of suspicion and good imaging during pregnancy are important in making this diagnosis.